Evaluation of prescription writing skills of medical professional practicing in varanasi city: A cross-sectional survey - Ananta Kusumakar; P G Naveen Kumar; Mahesh Ravindra Khairnar; Harloveen Sabharwal; Zainab Akram (Wolters Kluwer Medknow Publications, 2023)
Objective: Prescription writing is an integral part of medical profession. Incorrect prescription writing may lead to errors in instructions about the identity of the recipient, the identity of the drug, the formulation, dose, route, timing, frequency, and duration of administration. Hence, the present survey was undertaken to assess the prescription writing skills of doctors practicing in Varanasi city. Materials and Methods: This was a cross-sectional observational study, and 700 prescriptions dispensed by various doctors were collected for 7 consecutive days from 15 randomly selected pharmacy shops. Collected prescriptions were assessed for patient's information, doctor's information, and their legibility using predefined criteria by a calibrated examiner. Results: All the collected prescriptions lacked one or more aspects of patient's or doctor's details. About 46.2% of prescriptions lacked details about one or more drugs. Conclusion: Regarding the legibility of the prescription, it requires awareness programs for doctors to improve the quality of prescriptions. Changes in the registration system can be helpful in preventing errors in the details of the patients and doctors.